2020
DOI: 10.12681/jhvms.25074
|View full text |Cite
|
Sign up to set email alerts
|

Association of herd management with the infestation of ticks in domestic goats

Abstract: Three-stage cluster random sampling was done for determination of the association of herd management with the prevalence of tick (Acari: Ixodidae) infestation in goats (Capra hircus) in southern Punjab, Pakistan. A total of 136 nomadic goat herds and settled farms were screened for ticks and related information like nature of herds, herd size, farming pattern, animal keeping, housing, floor pattern and hygienic measures and documented on a pre-structured questionnaire. In addition, participatory epidemiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…No signifi cant diff erences in the tick infestation rate were found between the sheep reared with other ruminants (mixed rearing system) and those reared separately (one species rearing system). Th is fi nding was in agreement with the report of Sajid et al (2020) who found no association between the tick infestation and rearing type (with other ruminants or separately).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No signifi cant diff erences in the tick infestation rate were found between the sheep reared with other ruminants (mixed rearing system) and those reared separately (one species rearing system). Th is fi nding was in agreement with the report of Sajid et al (2020) who found no association between the tick infestation and rearing type (with other ruminants or separately).…”
Section: Discussionsupporting
confidence: 92%
“…Although there is no association between the herd size and tick infestation, the prevalence of infestation was higher in the small-size herds (less than 70 animals) (70.8%) as compared with the medium (60%) and large size (66.7%) herds. Th is was comparable with the study conducted by Sajid et al (2020) in which they found that herds having 40 -60 goats showed the highest ticks infestation. Th is might be due to the fact that a large number of ticks were fed on a few animals, which increased the rate of infestation.…”
Section: Discussionsupporting
confidence: 88%
“…These debilitating illnesses cause morbidity, which causes temporary or permanent product loss [22]. Parasitism in the Modern World Camelids, which comprise both ecto-and endoparasites, is a major public health concern across the world [23], notably in developing countries such as Pakistan [24][25][26][27][28]. The hot humid climate in the riverine areas of Punjab province substantially encourages the growth and development of endo-and ectoparasites, which causes parasitism to be violent.…”
Section: Introductionmentioning
confidence: 99%